Pharmacological chaperones rescue cell-surface expression and function of misfolded V2 vasopressin receptor mutants - Morello, Jean-Pierre (American Society for Clinical Investigation, 2000)
Over 150 mutations within the coding sequence of the V2 vasopressin receptor (V2R) gene are known to cause nephrogenic diabetes insipidus (NDI). A large number of these mutant receptors fail to fold properly and therefore are not routed to the cell surface. Here we show that selective, nonpeptidic V2R antagonists dramatically increase cell-surface expression and rescue the function of 8 mutant NDI-V2Rs by promoting their proper folding and maturation. A cell-impermeant V2R antagonist could not mimic these effects and was unable to block the rescue mediated by a permeant agent, indicating that the nonpeptidic antagonists act intracellularly, presumably by binding to and stabilizing partially folded mutants. In addition to opening new therapeutic avenues for NDI patients, these data demonstrate that by binding to newly synthesized mutant receptors, small ligands can act as pharmacological chaperones, promoting the proper folding and maturation of receptors and their targeting to the cell surface.